Grass Pollen Count and Grass group 5-allergen Release across Eight European Countries: results from HIALINE - Buters, Jeroen M. (2013)
Background: Grass pollen is considered to be the most important outdoor aeroallergen in Europe. The grass ‘pollen count’ is usually used as a proxy for exposure. However, HIALINE has shown that the birch and olive pollen count is not always congruent with allergen concentrations. We therefore simultaneously measured daily exposure to grass pollen and the concentration of group 5 major allergens across eight countries in Europe during 2009– 2011. Method: Airborne allergens were collected using a high-volume cascade impactor for particulate matter (PM) >10 lm and 10 lm > PM > 2.5 lm. Grass group 5 allergens (Phl p 5) were determined by ELISA. Airborne pollen was collected using Hirst-type volumetric pollen traps. The System for Integrated modeLing of Atmospheric coMposition (SILAM) was used to compute the origin of the collected pollen. Results: Allergen was recovered for >85% from the PM > 10 lm fraction of ambient air, showing that airborne allergen stems solely from pollen. On average pollen released 2.64 pg Phl p 5/pollen, comparable to birch and olive pollen. However, there was considerable variation between countries and between years. For instance in Evora, Portugal and Parma, Italy grass pollen released on average 40% less allergen per pollen than the European mean. When comparing individual years, the differences were up to 700% (Italy 2011 vs UK, 2009). This analysis concerns the comparison of yearly averages, which in themselves are already the average of approximately 60 days. Between days, between countries, the differences were even more extreme. Conclusion: Grass pollen released different amounts of group 5-allergens depending on the country, year and day. We believe that allergen release per pollen is determined by different grass species in different countries with different environmental conditions determines Phl p 5 release per pollen. It is unknown how well the surrogate marker pollen count represents allergy relevant exposure. Our data shows that in addition to variations in pollen exposures, there are also substantial allergen release variations on top.